Pelatihan Pembuatan Aplikasi Berbasis Android Pada SMK Teladan Pematangsiantar - Solikhun; Freshtiya Beby Larasati; Juni Ismail (Forum Kerjasama Pendidikan Tinggi, 2021)
SMK Teladan is the Best Vocational School in Pematangsiantar City. SMK Teladan are in great demand by the public in Pematagsiantar City and Simalungun Regency. SMK Teladan has several majors, one of which is Software Engineering and Computer Network Engineering. At the end of each academic year, the Student Competency Test is held for class XII students. Students in facing the the Student Competency Test Exam must be equipped with good competencies. This motivates to conduct training on making android applications. The software used is Android Studio and Figma. The purpose of this training is to equip students with the competence to make Android applications with Figma designs.